"Avoiding The Ultimate Break-Up" After Infidelity: The Marketisation of Counselling and Relationship-Work for Women in a South African Advice Column (1) - Wilbraham, Lindy (PINS-Psychology in Society, 2026)
This paper uses a Foucauldian discourse analytic approach to amplify, through exploration of the structuring effects of discourse, the relationship between psychologized knowledges about monogamy rules, counselling technologies and women’s subject positioning within Hallway’s Have-hold discourse. The formal features and narrative of an advice text from Couple Clinic, a specialist site of psychological advice about "relationship crises" in a South African women’s magazine, constitute the object of interpretative analysis. The ways in which women readers are impelled to labour on themselves and their (heterosexual) relationships to effect normalization after an instance of a male partner’s sexual infidelity are examined. Psychotherapeutic technologies produce rewards of power for women, and these powers are critically discussed in terms of various readings of and strategies for women’s empowerment in a South African context.